Vitamin D attenuates rhinovirus-induced expression of intercellular adhesion molecule-1 (ICAM-1) and platelet-activating factor receptor (PAFR) in respiratory epithelial cells - Greiller,CL; Suri,R; Jolliffe,DA; Kebadze,T; Hirsman,AG; Griffiths,CJ; Johnston,SL; Martineau,AR (Journal of Steroid Biochemistry and Molecular Biology, 2019)
Human rhinoviruses commonly cause upper respiratory infections, which may be complicated by secondary bacterial infection. Vitamin D replacement reduces risk of acute respiratory infections in vitamin D-deficient individuals, but the mechanisms by which such protection is mediated are incompletely understood. We therefore conducted experiments to characterise the influence of the major circulating metabolite 25-hydroxyvitamin D (25[OH]D) and the active metabolite 1,25-dihydroxyvitamin D (1,25[OH]2D) on responses of a respiratory epithelial cell line (A549 cells) to infection with a major group human rhinovirus (RV-16). Pre-treatment of A549 respiratory epithelial cells with a physiological concentration (10-7M) of 25(OH)D induced transient resistance to infection with RV-16 and attenuated RV-16-induced expression of the genes encoding intercellular adhesion molecule 1 (ICAM-1, a cell surface glycoprotein that acts as the cellular receptor for major group rhinoviruses) and platelet-activating factor receptor (PAFR, a G-protein coupled receptor implicated in adhesion of Streptococcus pneumoniae to respiratory epithelial cells). These effects were associated with enhanced expression of the genes encoding the NF-κB inhibitor IκBα and the antimicrobial peptide cathelicidin LL-37. Our findings suggest possible mechanisms by which vitamin D may enhance resistance to rhinovirus infection and reduce risk of secondary bacterial infection in vitamin D-deficient individuals.